The impact of patient heterogeneity and socioeconomic factors on abatacept retention in rheumatoid arthritis across nine European countries. Issue 1 (30th April 2015) - Finckh, A; Neto, D; Iannone, F; Loza, E; Lie, E; van Riel, P; Hetland, M L; Pavelka, K; Gottenberg, J E; Canhão, H; Mariette, X; Turesson, C
Abstract : Background: There are substantial differences in accessibility to biological disease modifying antirheumatic drugs (bDMARDs) across countries. The objective of this study was to analyse the impact of patient demographics, disease characteristics and gross domestic product (GDP) on abatacept (ABA) retention in patients with rheumatoid arthritis (RA) treated in clinical practice. Methods: Data from nine European observational RA cohorts of patients treated with ABA were pooled. Kaplan-Meier analysis was used to compare drug retention across registries. Specific causes of drug retention were investigated using competing risks multivariate Cox regression. Results: A total of 3961 patients treated with ABA, with 6188 patient-years of follow-up, were included. Patients in the different national registries had similar demographic features, but varied in baseline disease characteristics. ABA drug retention differed between countries, with median drug retention rates ranging from 1.2 to more than 6 years. The differences in drug retention were marginally explained by disparities in disease characteristics, while the national GDP per capita was strongly associated with drug retention (correlation coefficient −0.74; p=0.02). Conclusions: Patient characteristics at ABA initiation vary across Europe, probably reflecting differences in eligibility criteria and prescription patterns. However, the difference in ABA drug retention between countries was not primarily explained by disparities in patient characteristics. Lower ABA retention was observed in countries with a more liberal access to bDMARDs and higher GDP. National differences need to be accounted for when pooling data on treatment with bDMARDs from various countries.